2018
DOI: 10.1002/jcb.27405
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: KDM6B promotes ovarian cancer cell migration and invasion by induced transforming growth factor‐β1 expression

Abstract: KDM6B, also known as JMJD3, is a member of the family of histone lysine demethylase (KDMs), which is closely related to many types of cancers. However, its role and the underlying mechanisms in ovarian cancer remain unknown. Here we show that KDM6B is elevated in epithelial ovarian cancer and its expression level is closely related with metastasis and invasion. In addition, survival analysis showed that high expression of KDM6B was associated with low overall survival in ovarian cancer patients. Overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Notably, based on intensive studies across a broad spectrum of tumors 40 , 41 , the functional roles of both KDM6A and KDM6B in tumorigenesis were found to be highly cell type-specific and pathologic context-dependent. For instance, KDM6B could promote TGF-β-induced epithelial-mesenchymal transition (EMT) through activating SNAI1 in breast cancer cells 42 , and instigate proliferative, metastatic, and self-renewal capacities of tumor cells in liver, ovarian, and skin cancers by modulating multiple signalings 24 , 43 , 44 . On the other side, the tumor-suppressive role of KDM6B was supported by the evidence showing that it is a key activator of the INK4a / ARF tumor suppressor locus in response to oncogenic stress such as RAS activation 45 and it is involved in the epigenetic regulation of cis-regulatory elements activated during DNA damage response in a p53-dependent manner 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, based on intensive studies across a broad spectrum of tumors 40 , 41 , the functional roles of both KDM6A and KDM6B in tumorigenesis were found to be highly cell type-specific and pathologic context-dependent. For instance, KDM6B could promote TGF-β-induced epithelial-mesenchymal transition (EMT) through activating SNAI1 in breast cancer cells 42 , and instigate proliferative, metastatic, and self-renewal capacities of tumor cells in liver, ovarian, and skin cancers by modulating multiple signalings 24 , 43 , 44 . On the other side, the tumor-suppressive role of KDM6B was supported by the evidence showing that it is a key activator of the INK4a / ARF tumor suppressor locus in response to oncogenic stress such as RAS activation 45 and it is involved in the epigenetic regulation of cis-regulatory elements activated during DNA damage response in a p53-dependent manner 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of JMJD3 was also proved to be associated with Poor prognosis in ovarian cancer patients. Overexpression of JMJD3 promoted EMT, proliferation, invasion and migration of epithelial ovarian cancer cells in vitro , and enhanced metastatic capacities in vivo by promoting the growth factor-β (TGF-β1) expression (Liang et al 2019).…”
Section: Jmjd3 In Cancermentioning
confidence: 99%
“…In particular, upregulated DEGs included SIRT1 , which is involved in stemness [ 28 ] and chemoresistance [ 29 ], SNAIL2, which participates in EMT and collagen remodeling [ 30 , 31 ], and SIRT2 , CTGF , IL-11 and MMP13 , involved in cell migration, invasiveness as well as resistance to platinum and paclitaxel [ 32 , 33 , 34 , 35 , 36 ]. Other upregulated DEGs, such as MCM-6 , TGFB-1 , HMGA2 and FOXM1 , are involved in similar cancer-related processes [ 37 , 38 , 39 , 40 , 41 , 42 ], while downregulated DEGs, such as LOX and TIMP-1 (which are associated with poor cancer prognosis [ 43 , 44 , 45 ]), were observed in A2780 co-cultured with both A1 and A2 derived ML-Ddx4 + cells. Among these gene expression alterations, only ADGRL2 and PES1 upregulation were observed in A2780 cells conditioned with control ML-Ddx4 + cells, in a similar fashion to what emerged from the A1-related co-culture.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we also investigated the transcriptomic modifications of a panel of genes enrolled in major functions of the OC progression, and observed that ML-Ddx4 + cells from both OC subgroups, namely A1 and A2, deregulated in A2780 cells several key genes involved in ovarian carcinogenesis ( Figure 5 and Table 2 , Table 3 and Table 4 ). Among these, while in cells conditioned by ML-Ddx4 + cells from the A1 patient we revealed DEGs FOXM1 , HMGA2 and TGF-B1 involved in the modulation of EMT, tumor cell migration and invasiveness [ 38 , 40 , 41 ], those related to the ML-Ddx4 + cells from the A2 patient included ZFN703 , SSTR2 and MMP13 , which regulate OC proliferation, chemoresistance and prognosis [ 53 , 54 , 55 ]. However, besides these DEGs, which were separately registered in experiments using ML-Ddx4 + cells from A1 and A2 OC patients, several deregulated genes were shared between A2780 cells conditioned by each ML-Ddx4 + population.…”
Section: Discussionmentioning
confidence: 99%